Perceptions of classroom quality and well-being among Black women teachers of young children - Edwards, Erica B.; Patton Terry, Nicole; Bingham, Gary; Singer, Jeremy L. (Education Policy Analysis Archives, 2021)
Concerns about preschool effectiveness have increasingly led to early childhood education policy changes focused on teacher quality. While these reforms intend to ensure children’s educational well-being, they rarely consider the impact policies have on teachers. Additionally, child care work is a feminized profession with distinct social experiences along lines of race and class. Black women who are early child care teachers live in poverty at rates disproportionate to their white counterparts. Through Black feminist focus group research, this paper documents perceptions of early childhood education quality mandates in Georgia and their impact on the well-being of 44 Black women teachers of infants, toddlers, and preschool age children. Findings suggest that the call for quality complicates Black teachers’ work, adds undue financial and emotional stress that takes a toll on their well-being, and interrupts personal dynamics with their loved ones. The paper calls for antiracist and antisexist structural support to interrupt both the stressors exacted by the field and the sociohistorical processes devaluing Black women’s work with children.